A Review Study of the effect of COVID-19 on Diabetic patients - Al-Dedah, Rusul Malik; Raheem, Saif Ahmed (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Coronavirus disease 2019 (CoVID-19), which has spread widely around the world, has had a major impact on the health of individuals, especially those suffering from chronic diseases. One of these diseases is diabetes, which is considered one of the common diseases, main entry receptor for SARS-CoV-2 virus is Angiotensin-converting enzyme 2 (ACE2). Many patients with diabetes suffered from high blood sugar after their infected with Covid-19, in addition to the effect of insulin and its relationship to mortality. Studies have also indicated that chronic inflammation leads to the development of the disease and insulin resistance. Inflammation activating plasmin has an effect on D-dimer, leading to its increase، this increase also leads to mortality. Patients older than 50 years old were more likely to be affected by CoVID-19. The aim behind this study is to explore this link to be managed appropriately, as people with diabetes need to control their sugar levels because imbalances in these ratios may lead to an increase in the effects of covid-19 infection.